Исследование процесса карбонизации гидромоносиликата кальция в барботажном аппарате с провальными тарелками - Г. О. Григорян (ՀՀ ԳԱԱ հրատ.)
Изучено изменение степени карбонизации, количества поглощенного углекислого газа, содержания СО2 в осадке по высоте барботажного аппарата. Установлена зависимость коэффициента ускорения абсорбции от степени карбонизации. Определены оптимальные параметры карбонизации и предложен метод расчета общего коэффициента массопередачи процесса. Ուսումնասիրված է կալցիումի հիդրամետասիլիկատի կարբոնիզացիայի աստիճանը, կլանված ածխաթթու գազի քանակը, ինչպես նաև նստվածքում CO2-ի պարունակության կախումը կլանման աշտարակի բարձրությունից: Հաստատված են կարբոնիզացման պրոցեսի ընդհանուր օպտիմալ պայմանները: Առաջարկված է աբսորբցիոն պրոցեսի ընդհանուր մասսահաղորդման գործակցի հաշվարկման մեթոդ: Carbonization of calcium hydro-meta-silicate in the drift-plate apparatus was investigated. Kinetic and diffusion zones were identified in the curves describing the degree of carbonization of calcium hydro-meta-silicate vs. the coefficient of absorption rate relationship along the height of barbotage apparatus with drift-plates. The chemical reaction on the CSH particles’ surface is the rate-determining step in the first kinetic zone where C/S ratio in CSH decreases down to 0.8. Disintegration of the structure of CSH takes place in the second diffusion zone where both the chemical ration and diffusion are considered rate determining. Practically no chemical reaction occurs in the third diffusion zone where the process is to tally described by the retardation in the liquid film. The following optimal parameters were established for the process: liquid/solid mass ratio: 4.6-5.2; temperature: 50°C; concentration of carbon dioxide in gas-air mixture: 25-30 volume percent; degree of carbonization: 70-75 percent. The absorption coefficient of acceleration was calculated from the general coefficient of absorption and partial coefficient of mass transfer in the liquid phase determined at similar hydrodynamic conditions. A method for the calculation of general coefficient of absorption is proposed using both the partial coefficient of absorption in the liquid phase and the coefficient of absorption acceleration determined graphically from its dependence on temperature, on concentration of carbon dioxide in gas-air mixture and on the degree of carbonization.
Keywords: Chemistry